Benefits of Collaborative Philosophical Inquiry in Schools - Millett, Stephan; Tapper, Alan (Blackwell Publishing, 2011)
In the past decade well-designed research studies have shown that the practice of collaborative philosophical inquiry in schools can have marked cognitive and social benefits. Student academic performance improves, and so too does the social dimension of schooling. These findings are timely, as many countries in Asia and the Pacific are now contemplating introducing Philosophy into their curricula. This paper gives a brief history of collaborative philosophical inquiry before surveying the evidence as to its effectiveness. The evidence is canvassed under two categories: schooling and thinking skills; and schooling, socialisation and values. In both categories there is clear evidence that even short-term teaching of collaborative philosophical inquiry has marked positive effects on students. The paper concludes with suggestions for further research and a final claim that the presently-available research evidence is strong enough to warrant implementing collaborative philosophical inquiry as part of a long-term policy.